Trace of one : poems - Goodman, Joanna, 1968- (Iowa poetry prize., 2002)
In Trace of One, real geographies merge with spiritual ones, just as details of the speaker's physical and emotional worlds intertwine with the transcendent realms of science, religion, and myth. Joanna Goodman's poems share a sense of spatial and temporal displacement -- they are love poems to a place, whether it be a field, a room, or a paradise -- they celebrate their subjects, but they are also poems of grief and solitude.